2017
DOI: 10.1038/srep46153
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Cytokine Signaling 2 Negatively Regulates NK Cell Differentiation by Inhibiting JAK2 Activity

Abstract: Suppressor of cytokine signaling (SOCS) proteins are negative regulators of cytokine responses. Although recent reports have shown regulatory roles for SOCS proteins in innate and adaptive immunity, their roles in natural killer (NK) cell development are largely unknown. Here, we show that SOCS2 is involved in NK cell development. SOCS2−/− mice showed a high frequency of NK cells in the bone marrow and spleen. Knockdown of SOCS2 was associated with enhanced differentiation of NK cells in vitro, and the transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 47 publications
4
30
0
1
Order By: Relevance
“…This further implies the migration defects of both Raptor- and Rictor-deficient NK cells. Moreover, an increase in the transcript level of Socs2 in Rictor cKO NK cells ( Figure 5C ) may contribute to their impaired proliferation and reduced cellularity ( Kim et al, 2017 ). Related to NK cell effector functions, the RNA sequencing data revealed that Rictor, but not Raptor, deficiency results in reduced transcripts level of Ifng and Gzmb ( Figure 5B and C ).…”
Section: Resultsmentioning
confidence: 99%
“…This further implies the migration defects of both Raptor- and Rictor-deficient NK cells. Moreover, an increase in the transcript level of Socs2 in Rictor cKO NK cells ( Figure 5C ) may contribute to their impaired proliferation and reduced cellularity ( Kim et al, 2017 ). Related to NK cell effector functions, the RNA sequencing data revealed that Rictor, but not Raptor, deficiency results in reduced transcripts level of Ifng and Gzmb ( Figure 5B and C ).…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate the correlation between TXNIP and AKT, we examined whether TXNIP interacts with AKT in cells. TXNIP‐ and AKT‐overexpressing plasmids were cotransfected into 293T cells, and GST pull‐down assays were performed as previously described (Kim et al, 2017, 2017). TXNIP was found to interact with AKT (Supporting Information Figure S3A), which was also confirmed by immunoprecipitation assays in 293T cells (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…SOCS1 even prevents regulatory T (Treg) cells from producing IFN-γ by suppression of STAT1, avoiding the conversion of Treg cells into effector cells ( 106 ). In addition, SOCS2-deficient mice showed a reduction in lung metastases and an increase in survival following melanoma challenge ( 107 ).…”
Section: Canonical Signaling and Regulatory Mechanismsmentioning
confidence: 99%